Game Edukasi Penyelamatan Korban Bencana Gempa Bumi Berbasis Multiplatform - Rohman, Irfan Yanuar; , Endah Sudarmillah, S.T., M.Eng (2016)
An earthquake is a disaster that many casualties on the 2006 earthquake hit Java, earthquakes in the field in 2009 and the earthquake and tsunami in Aceh in 2004 that killed thousands of people and destroyed buildings. Ignorance about the earthquake itself is one of the causes of the many victims of both the injured and dead. For that we need education about the rescue of victims of the earthquake. Game is a means of entertainment that can be used as a medium of education because it is fun and easily recorded in the memory of the brain. With these authors would like to combine the game with earthquakes and produce an educational game about the rescue of earthquake victims as a media-based multiplatform interactive learning. This study uses the SDLC methodology with the waterfall model. The results of this study are educational games that have been filled with material about the rescue of earthquake victims are constructed using 2-based multiplatform construct that can be played on Windows-based desktop with berekktensi .exe files with mobile and android-based smartphone with a file extension .apk. This result has been tested reliability using the formula with the result cronbanch alpha alpha value 0.739, which means high to set the accuracy, stability dalama educational research. Interpretation and based on questionnaires percentage reached 91.5% which is where the figure scale interval 81-100% expressed strong.